I have a dream (Volume 8) - Vio, Bebe (European Investment Bank, 2019)
All athletes experience setbacks. But to have your limbs - the very tools you use to practice your sport - taken away by an illness at a young age is a setback that many would never overcome. Bebe Vio never gave up her dream of becoming a fencer, despite having her arms and legs amputated when she was eleven years old after suffering from fulminant meningitis. Instead of abandoning her dream of going to the Olympics, she began training for the Paralympics from a wheelchair. Her unwavering determination to win, despite her physical challenges, made her a world champion fencer. She also established her own association, art4sport, to encourage other people to pursue the beauty of life through sport. This is the eighth essay in the Big Ideas series created by the European Investment Bank. The EIB has invited international thought leaders to write about the most important issues of the day. These essays are a reminder that we need new thinking to protect the environment, promote equality and improve people's lives around the globe.